Applying cavity ring‐down spectroscopy for the measurement of dissolved nitrous oxide concentrations and bulk nitrogen isotopic composition in aquatic systems: Correcting for interferences and field application. (18th May 2015) - Erler, D. V.; Duncan, T. M.; Murray, R.; Maher, D. T.; Santos, I. R.; Gatland, J. R.; Mangion, P.; Eyre, B. D.
Abstract Laser spectroscopy is an emerging technology for measuring nitrous oxide (N2O) dynamics in the environment, but most studies have focused on atmospheric applications. We have coupled a commercially available cavity ring‐down spectroscope (CRDS) (Picarro G5101‐I isotopic N2O analyzer) to an air/water gas equilibration device to collect continuous in situ dissolved N2O molar concentration and bulk nitrogen isotopic (δ15N‐N2O) data. The δ15N‐N2O values measured by the CRDS unit were found to be significantly affected by changes in the mixing ratios of O2, CO, CH4, and CO2. There was also an effect of N2O mixing ratio on δ15N‐N2O. A series of equations was developed to correct for the matrix effect of O2 and the spectral interference by CH4. Chemical traps effectively prevented interferences by CO and CO2. The maximum corrections required for N2O mixing ratio and O2 matrix effects, were 1‰ (at a mixing ratio of 1.2 ppmv), and 11‰ (at 0% O2 content), respectively. The CH4 correction only became important at mixing ratios greater than 500 ppmv (>0.5‰). Measurements of N2O molar concentration and δ15N‐N2O from the CRDS isotopic N2O analyzer were similar to those measured with isotope ratio mass spectrometry. We demonstrated the utility of the laser‐based system with field deployments in three estuarine tidal creeks in subtropical Australia. Future work in this field should focus on the application of the laser‐based system to the measurement of N2O isotopologues in aquatic habitats, allowing for further constraints to be placed on the pathways of N2O cycling in aquatic system.